The Importance and Complexity of Assessing Urban Fiscal Health. (September 2016) - Helpap, David J.
The following is a review of Richard M. Bird and Enid Slack's edited volume Is Your City Healthy? Measuring Urban Fiscal Health . The review addresses major themes in the book as well as its place within existing scholarship.